Экстремальные задачи с коническими ограничениями - Ненахов, Э.И. (Теорія оптимальних рішень, 2006)
We consider nonlinear semidefinite problems. First-order optimality conditions are derived. An algorithm for solving convex programming with cone constraints is proposed. The algorithm globally converges. General parametric problem was investigated.